PEMBELAJARAN FISIKA DENGAN PENGGUNAAN KIT IPA DITINJAU DARI KETERAMPILAN PROSES DAN SIKAP ILMIAH SISWA KELAS X SMA DHARMA LOKA PEKANBARU - Nonny Komalasari Nonny Komalasari; Mitri Irianti Mitri Irianti; Yennita ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research aims to describe outcome of process skills and scientific attitudes students in tenth grade of Dharma Loka Senior High School Pekanbaru using KIT IPA on Matter and Heat topic. The method used in this research is Pre-Experimental Design and was conducted by the research design One Shot Case Study. Data collection instrument in this research is the process skills test and scientific attitude questioners. Analysis of the data in this research is a descriptive analysis for describe process skills and scientific attitudes. From the analysis of process skills data showed: the average absorption is 82 % with good category; effectiveness is 82% is categorized effective learning; completeness learning material is 100% with complete category. While analysis of the data in scientific attitudes is 81% with very good category. So it can conclude that outcome of process skills and scientific attitudes students in tenth grade of Dharma Loka Senior High School Pekanbaru using KIT IPA at Matter and Heat topic is very good. Key Words : kit ipa, process skills,scientific attitude, matter and heat